COVID-19 Pulmonary Failure and Extracorporeal Membrane Oxygenation: First Experience from Three European Extracorporeal Membrane Oxygenation Centers - Yankah, Charles Abraham; Trimlett, Richard; Sandoval, Elena; Lotz, Christopher; Ledot, Stephane; Pomar, Jose Luis; Price, Susanna; Meybohm, Patrick (The Thoracic and Cardiovascular Surgeon, 2020)
On April 17, 2020, a coronavirus disease 2019 (COVID-19) webinar was held by selected international experts in the field of intensive care and specialized respiratory ECMO centers from Germany, Italy, Spain, and the United Kingdom, which was hosted by the German Heart Centre Berlin/Charité. The experts shared their experience about the treatment of 42 patients with severe acute respiratory failure requiring venovenous extracorporeal membrane oxygenation (VV-ECMO). Patients were predominantly male (male-to-female ratio: 3:1), with a mean age of 51 years (range: 25–73 years). VV-ECMO support was indicated in 30% of the ventilated COVID-19 patients. The mean time requiring mechanical ventilation was 16.5 days, with a mean duration of ECMO support of 10.6 days. At the time of the webinar, a total of 17 patients had already been decannulated from ECMO, whereas six died with multiorgan failure. 18 patients remained on ECMO, with their final outcomes unknown at the time of the webinar. Hospital mortality was 25.6% (as of April 17, 2020). In this respect, VV-ECMO, provided by expert centers, is a recognized and validated mode of advanced life-support during the recent COVID-19 pandemic with good outcomes.
Keywords: acute respiratory failure; C-ARDS; advanced life support; VV ECMO, VA ECM; pulmonary thrombosis (microthrombosis, systemic microthrombosis, thrombolysis)